Controlling the White‐Light Generation of [(RSn)4E6]: Effects of Substituent and Chalcogenide Variation. Issue 47 (15th October 2019) - Dornsiepen, Eike; Dobener, Florian; Chatterjee, Sangam; Dehnen, Stefanie
Abstract: Adamantane‐type organotin chalcogenide clusters of the general composition [(RT)4 S6 ] (R=aromatic substituent, T=Si, Ge, Sn) have extreme non‐linear optical properties that lead to highly directional white‐light generation (WLG) upon irradiation with an IR laser diode. However, the mechanism is not yet understood. Now, a series of compounds [(RSn)4 E6 ] (R=phenyl, cyclopentadienyl, cyclohexyl, benzyl, CH2 CH2 (C6 H4 )CO2 Et; E=S, Se), were prepared, characterized, and investigated for their nonlinear optical properties. With the exception of crystalline [(BnSn)4 S6 ], all these compounds exhibit WLG with similar emission spectra; slight blue‐shifts are observed by introduction of cyclopentadienyl substituents, while the introduction of Se in the inorganic core can provoke a red‐shift. These investigations disprove the initial assumption of an aromatic substituent being a necessary precondition; the precondition seems to be the presence of (cyclic) substituents providing enough electron density. Abstract : In search of the preconditions for the generation of highly directed white light by means of amorphous molecular materials of the general formula [(RT)4 E6 ] (R=organic group, T/E=Group 14/16 elements), nine new compounds were studied. Surprisingly, R does not need to be an aromatic ligand, in striking contrast to previous assumptions.